2005
DOI: 10.1007/s00264-005-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of osteoporotic hip fractures in Spain

Abstract: We conducted a multicentre study, divided into a retrospective and a prospective portion. The retrospective study evaluated osteoporotic hip fractures that occurred during 2002. The prospective study evaluated osteoporotic hip fractures that occurred during May 2003. The study was conducted in 77 hospitals in Spain and comprised patients 60 years of age and over. In the retrospective study we registered 13,195 hip fractures. Of the patients, 74% were women and 26% were men. The mean age was 80.7±8.4 years. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
(26 reference statements)
2
21
0
8
Order By: Relevance
“…Previous studies have shown that the prevalence of osteoporosis varies among the different geographic areas due to ethnic and environmental factors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Having an estimate of the incidence of osteoporosis, based on the number of hip fracture in subjects aged over 50 years is therefore essential to estimate the risk of osteoporosis of the population and the economic impact of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the prevalence of osteoporosis varies among the different geographic areas due to ethnic and environmental factors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Having an estimate of the incidence of osteoporosis, based on the number of hip fracture in subjects aged over 50 years is therefore essential to estimate the risk of osteoporosis of the population and the economic impact of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for us lies in efficient use of the limited resources available to provide high quality care based on clinical evidence. A great deal of work has already been done in the West on the functional outcome of hip fractures [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Herrera et al 14 5 inhabitants/year 2010, respectively. In this work, a downward trend was observed in the incidence of hip fracture in women 65 to 80 years old accompanied by a significant increase after 85 years in both sexes.…”
Section: National Studiesmentioning
confidence: 99%